Evolution, Suffering, Omniscience and the Kenosis of Jesus Christ –Attempts at a Synthesis - May, Andreas (Sekolah Tinggi Teologi Simpson Ungaran, 2025)
At present, an intensive search is underway for a synthesis that satisfactorily explains the existence of evil and suffering against the background of the evolution of living beings and essential attributes of the Christian God. The methodological approach of this paper was to combine fundamental statements of the Christian faith, results of research in modern theological and philosophical publications, and findings of the natural sciences. The first attempt explains suffering and evil in the world in terms of evolution and human free will. The second attempt also takes into account the Angelic Fall and the Adamic Fall. The third attempt adds the following working hypothesis: God the Father is timeless. In contrast, God the Son, as part of his kenosis, subjected himself to time not only during his life as a human being on Earth, but also before and after. Various consequences of this working hypothesis were considered. The contribution of this working hypothesis is that it resolves the conflict between the free will of creatures and the omniscience of God and explains some other theological questions: The incarnation of Jesus Christ as a response to the Fall, the intra-Trinitarian dialogue and the significance of God the Father for creation.